N‐Doped Graphene Decorated with Fe/Fe3N/Fe4N Nanoparticles as a Highly Efficient Cathode Catalyst for Rechargeable Li−O2 Batteries. Issue 17 (14th June 2018) - He, Lewei; Wang, Gan; Wu, Xiangwei; Wen, Zhaoyin; Zhang, Wenqing
Abstract: The development of low‐cost and highly efficient electrocatalysts for the widespread application in rechargeable Li‐O2 batteries is still a major research challenge. Herein, porous N‐doped graphene, decorated with Fe/Fe3 N/Fe4 N nanoparticles is designed and synthesized via a one‐step pyrolysis of easily available precursors. It is found that the Fe/Fe3 N/Fe4 N nanoparticles are uniformly dispersed on the N‐doped graphene substrate, and that both the nanoparticles and the substrate can facilitate the electrochemical reaction. When the rationally designed material is used as cathode in Li‐O2 batteries, it exhibits excellent electrochemical performance, delivering a high capacity of 7397.8 mAh g −1 and showing impressive cycle stability of over 100 steady cycles. The excellent performance of this material is attributed to the good synergistic effect of uniformly distributed nanoparticles and the porosity of the substrate. These results indicate that the N‐doped graphene decorated with Fe/Fe3 N/Fe4 N is an excellent cathode catalyst for Li‐O2 batteries and would also be a promising new material for other energy storage devices. Abstract : Synergy is the key : a composite material of Fe/Fe3 N/Fe4 N nanoparticles and N‐doped graphene is prepared as efficient electrocatalyst for rechargeable Li‐O2 batteries. The high activity of the Fe/Fe3 N/Fe4 N nanoparticles facilitates the cathode reaction kinetics, and the appropriate microstructure of the N‐doped graphene substrate ensures the transport and storage of the reaction substances.